2008
DOI: 10.1044/0161-1461(2008/007)
|View full text |Cite
|
Sign up to set email alerts
|

Training and Knowledge in Autism Among Speech-Language Pathologists: A Survey

Abstract: The return rate for participants was small, and it is difficult to generalize the results. However, the majority of respondents reported that they could have benefited from additional training in the area of autism. As a result, it may be necessary to consider strategies for providing this training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
84
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(93 citation statements)
references
References 17 publications
8
84
1
Order By: Relevance
“…Previous studies have documented the large caseloads of school-based speech-language pathologists (SLPs) (ASHA, 2009) as well as the shortage of SLPs with expertise in either AAC (Simpson, Beukelman, & Bird, 1998) or ASD (Schwartz & Drager, 2008). Given these constraints, it is imperative that the time spent by SLPs whose caseloads include students who require AAC be both effective and efficient.…”
Section: Implications For Practicementioning
confidence: 99%
“…Previous studies have documented the large caseloads of school-based speech-language pathologists (SLPs) (ASHA, 2009) as well as the shortage of SLPs with expertise in either AAC (Simpson, Beukelman, & Bird, 1998) or ASD (Schwartz & Drager, 2008). Given these constraints, it is imperative that the time spent by SLPs whose caseloads include students who require AAC be both effective and efficient.…”
Section: Implications For Practicementioning
confidence: 99%
“…14,15 The focus of these surveys has focused on a combination of specific geographic locations, communication modes, and/or ages. For example, Binger and Light 16 surveyed 144 speech-language pathologists (SLP) providing services to preschoolers using AAC in Pennsylvania and found that 12.5% of students receiving special education services required AAC.…”
mentioning
confidence: 99%
“…Although students may acquire this competency by working with individuals with ASD, it is entirely possible that they will graduate without adequate knowledge in ASD unless university programs build it into their curriculum. Access to such preparation is not found in all accredited graduate programs despite a desire from SLPs to have additional specialized training [3,7] and the increased levels of comfort that accompany that training [8]. Some institutions, Brooklyn College, for example, have implemented a specialized certificate [9] while others have more recently begun to offer specialized coursework.…”
Section: Introductionmentioning
confidence: 99%
“…For example, students may believe that diet modifications are effective in all cases [11]. Other areas requiring further instruction based on the prior literature were related to genetics of ASD and diagnostic criteria [3,7,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation